2017
DOI: 10.21608/ejnf.2017.103924
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zinc Supplementation on Performance of Growing Lambs

Abstract: his study was investigated to determine the effect of zinc source either from organic or inorganic on lambs performance, blood metabolites and carcass characteristics. Fifteen local lambs (about six months old and an average body weight of 26.5± 3.1 kg) were divided into three similar groups (5 lambs each). The control group (G1) was fed the basal diet consisting of wheat straw and concentrates mixture. While, the other two tested groups were fed the same basal diet, supplemented with 20 mg Zn/head/day as Zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…These results agree with those obtained by Gaafar et al (2018) who showed that Spirulina additive resulted in significant (P<0.05) improvements in economic efficiency. Similar results were recorded by Hafez et al (2013) who found markedly positive effect on economic efficiency due to Spirulina algae supplementation into the rations of growing lambs. Moreover, with dairy goats Khalifa et al (2016) revealed that a marked improvement in economic efficiency when added 500 mg of Spirulina powder into the control diet (100.00 vs 127.27%).…”
Section: Economic Efficiencysupporting
confidence: 88%
See 1 more Smart Citation
“…These results agree with those obtained by Gaafar et al (2018) who showed that Spirulina additive resulted in significant (P<0.05) improvements in economic efficiency. Similar results were recorded by Hafez et al (2013) who found markedly positive effect on economic efficiency due to Spirulina algae supplementation into the rations of growing lambs. Moreover, with dairy goats Khalifa et al (2016) revealed that a marked improvement in economic efficiency when added 500 mg of Spirulina powder into the control diet (100.00 vs 127.27%).…”
Section: Economic Efficiencysupporting
confidence: 88%
“…Current results are consistent with the findings that recognized by Hassanien et al (2015) who worked with goats and used Spirulina algae at 0.2% of their feed intake. Likewise, Hafez et al (2013) found that blood total protein and albumin concentrations were significant higher with 0.2% Spirulina platens algae of DMI of growing lambs than those of control diet that free from algae supplement. In addition, the rest of blood parameters (globulin, cholesterol, triglycerides, creatinine, urea-N, AST and ALT) concentrations did not affect by dietary algae supplements.…”
Section: Blood Constitutesmentioning
confidence: 84%
“…Zarczynska and Krzebietke (2020) noted that it has been discovered that Cr helps ruminants to grow and convert more feed into energy. Additionally, Farghaly et al (2017) observed that the average daily gain (ADG) of the control group was lower than that of the Zn-SO4 and Zn-Met groups. Zinc sulphate and zinc methionine, when given to meals as dietary supplements, boosted lambs' average daily growth by roughly 25 and 24%, respectively, in comparison with the control group.…”
Section: Growth Performancementioning
confidence: 98%